The rise of the U.S. environmental health movement - Davies, Kate, 1956- (Rowman and Littlefield Publishers, Incorporated, 2013)
This is the first book to offer a comprehensive examination of the Environmental Health Movement, which unlike many parts of the environmental movement, focuses on ways toxic chemicals and other hazardous agents in the environmental effect human health and wellbeing.